ChemInform Abstract: Tailor‐Made Ruthenium‐Triphos Catalysts for the Selective Homogeneous Hydrogenation of Lactams. Issue 22 (12th May 2016) - Meuresch, Markus; Westhues, Stefan; Leitner, Walter; Klankermayer, Juergen
Abstract: The novel catalyst (RUT) shows increased activity and selectivity and facilitates the hydrogenation of challenging lactams.